Surgical Techniques for Head and Neck Reconstruction in the Vessel-Depleted Neck - Martinez, Daniel C.; Badhey, Arvind; Cervenka, Brian; Zender, Chad; Tang, Alice; Patil, Yash (Facial Plastic Surgery, 2020)
The vessel-depleted neck presents a unique and challenging scenario for reconstructive surgery of the head and neck. Prior surgery and radiation often result in significant scarring and damage to the neck vasculature, making identification of suitable recipient vessels for microvascular free tissue transfer exceedingly difficult. Therefore, alternative reconstructive techniques and/or vessel options must be considered to obtain a successful reconstructive outcome for a patient. In this article, we discuss our experience and approach to the management of the vessel-depleted neck, emphasizing the importance of preoperative planning and having multiple backup options prior to surgery. The various preoperative imaging modalities and available options for recipient arteries and veins are presented in detail. Additionally, we discuss modifications of select free flaps to maximize their utility in successful reconstruction. Together with thoughtful preoperative planning, these techniques can help aid the reconstructive surgeon in addressing the complex decisions associated with the vessel-depleted neck.
Keywords: vessel-depleted neck; salvage surgery; microvascular reconstruction; free tissue transfer; head and neck surgery